Mobilização do solo na semeadura do milho: emissão de CO2 e desempenho de máquinas agrícolas - Bertonha, Rafael Scabello [UNESP] (2015)
The soil tillage systems for grain crops deploying are of great importance, since crop development and performance of agricultural machinery to the soil and water conservation. Therefore, for the producer who want to cultivate grain crops, he needs before to get knowledge about soil, the tool type to prepare it, the ideal machine for the power utilization and the contribution to the environment that soil tillage system chosen will provide. This study carried out three experiments that the aim was to evaluate the soil CO2 emission, the performance of agricultural machines and the corn crop development as a function of the disturbed soil amount by furrow opener hoe type in no-tillage system and subsoiler opener in strip-tillage system. In the first study we used three planter furrow opener hoe type (H1: inclined at 17° rake angle; H2: straight, with inclined tip and 29° rake angle and H3: parabolic and 27° rake angle) and five working depths (5.5, 9.0, 12.5, 16.0 and 19.5 cm). In the second study we used the H1 opener in three working depths (9.0, 12.5 and 16.5 cm) and four water content of the soil (WCS 1, 2, 3 and 4), it being dryer in WCS1 and wetter in WCS4. Both of these studies was carried out in eutroferric Red Latosol and no-tillage system with more than 8 years (Jaboticabal city, São Paulo, Brazil). In the third study we used a subsoiler opener at three working depths (26.0, 32.0 and 38.0 cm) in strip-tillage system, in a Dothan sandy loam (north Florida, USA). For the first study, the geometry of the opener directly affected soil disturbance, machine performance and the crop development. However, we suggested that the inclined opener with 17° rake angle, working at greater depths, because this combination presented lower fuel consumption per volume of disturbed soil without reducing crop yields. For the second study, the opener disturbed more soil at greater depths, but this increase was not proportional from the ...